THE IMPLEMENTATION OF INQUIRY MODELS TO IMPROVE ACCURACY AND STUDENT LEARNING ACHIEVEMENT (Case Study on science subject of seventh class in SMPN 05 Lebong ) - Leli Yatima; Johanes Sapri (DIADIK, 2019)
This study purpose to describe the implementation of the inquiry model in science learning to improve accuracy of students in seventh class in SMPN 05 Lebong, describing the implementation of the inquiry model achievement in seventh class in SMPN 05 Lebong, describing the effectiveness of the implementation inquiry model in improving student science learning achievement of seventh class in SMPN 05 Lebong the research conducted classroom action research combined with quasi- experiment. Subject of this studywas seven one PTK class, seven three experimental class, while class seven four is control class. The instruments used are observation and test sheets. Data analysis techniques use the average formula and t-test, while the observation data are analyzed by difference in score and range of values for each criterion. The results of the study show that the